2018
DOI: 10.1088/1361-648x/aaf4c4
|View full text |Cite
|
Sign up to set email alerts
|

Mode confinement, interface mass-smudging, and sample length effects on phonon transport in thin nanocomposite superlattices

Abstract: We employ a semi-ab initio theoretical method to investigate mode confinement, interface mass-smudging, and sample length effects on phonon transport in thin nanocomposite superlattices. We present a detailed comparative study of numerical results showing the reduction in thermal conductivity due to each of these three effects for Si/Ge nanocomposite structures with planar superlattice (SL), embedded nanowire superlattice (NWSL), and embedded nanodot superlattice (NDSL) geometries. Importantly, it is found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Region R2 (D ∼ Λ) : κ = κ(a suitable effective medium expression), For ultra short period nanocomposites, we calculate κ(D << Λ) using our semi-ab initio approach for the DFT-Boltzmann based conductivity tensor [11,20] and a generalised version of Callaway's anharmonic phonon relaxation time expression [19] using phonon eigensolutions generated using Density Funtional Peturbation Theory [21]. A recap of the essential features is presented in Appendix A.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Region R2 (D ∼ Λ) : κ = κ(a suitable effective medium expression), For ultra short period nanocomposites, we calculate κ(D << Λ) using our semi-ab initio approach for the DFT-Boltzmann based conductivity tensor [11,20] and a generalised version of Callaway's anharmonic phonon relaxation time expression [19] using phonon eigensolutions generated using Density Funtional Peturbation Theory [21]. A recap of the essential features is presented in Appendix A.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Phonon eigensolutions required for the thermal conductivity calculations were generated using the Quantum Espresso package [21] with parameters defined in previous studies [11,20,30]; some quantitative corrections from previously reported thermal conductivity results are due to this study's work using the correct eigenvalue input as per recent work [26].…”
Section: Generation Of Phonon Eigensolutionsmentioning
confidence: 99%
See 3 more Smart Citations